Charge Trapping Analysis of Metal/Al2O3/SiO2/Si, Gate Stack for Emerging Embedded Memories - Khosla, Robin; Rolseth, Erlend Granbo; Kumar, Pawan; Vadakupudhupalayam, Senthil Srinivasan; Sharma, Satinder K.; Schulze, Jörg (IEEE Transactions on Device and Materials Reliability, 2017)
For Al2O3 charge trapping analysis, Metal/Al2O3/SiO2/Si (MAOS) structures are fabricated from atomic layer deposition and plasma enhanced chemical vapor deposition-based Al2O3 and SiO2 thin films, respectively. The fabricated MAOS devices showed high memory window of 7.81V@16V sweep voltage and leakage current density of sim 3.88times 10-6textA/cm 2 @-1V. The charge trapping and decay mechanism are investigated with the variation of alumina thickness by Kelvin probe force microscopy (KPFM). It reveals that vertical charge decay is a dominant phenomenon of charge loss for Al2O3 in contrast to lateral charge spreading. Constant current stress (CCS) measurements mark the location of charge trap centroid at 10.30 nm from metal/Al2O3 interface attributes that bulk traps present close to the Al2O3/SiO2 interface are dominant charge trap centres. In addition, a simple method is proposed to estimate the trap density using KPFM and CCS method at room temperature. Furthermore, there is 28% exponential decay in high state capacitance observed after 104 s in capacitance-time analysis at room temperature. This material engineering of charge traps will improve the performance and functionality of bilayer Al2O3/SiO2 structure for embedded memory applications.
CRIS-Team Scopus Importer:2021-06-29
Keywords: aluminium oxides (Al2O3); atomic layer deposition (ALD); Charge trapping; high-κ; Kelvin probe force microscopy (KPFM); memory